Load-Bearing Capacity and Design Advantages of a Custom-Made, Thin Pure-Titanium Cranioplasty (CranioTop). Issue 4 (June 2021) - Lewitz, Marc; Salma, Asem; Welzel Saravia, Heinz; Sakellaropoulou, Ioanna; Sarkis, Hraq Mourad; Ewelt, Christian; Fortmann, Thomas; Wilbers, Eike; Schipmann, Stephanie; Suero Molina, Eric; Santacroce, Antonio; Zawy Alsofy, Samer
Abstract : Background: Adequate and stable coverage of cranial contour and continuity defects of any origin is a common challenge in neurosurgical clinics. This study presents the results of investigations concerning the mechanical load-bearing capacity and design advantages of custom-made implants made from a thin, pure-titanium sheet (CranioTop) (CLinstruments, Attendorn, Germany) for covering complex cranial defects. Methods: In 9 test series, the stability of three differently shaped and sized thin titanium sheet implants was tested using vertical, uniaxial compression with 3 different compression stamps, to investigate the behaviour of these implants in relation to punctiform as well as planar forces. Results: All 9 model implants showed elastic behavior in the synchronously recorded force/displacement diagrams at an impression of up to 2 mm. The forces at 2 mm deformation were between 170.1 and 702.7 Newton. Conclusion: Cranioplasty using CranioTop is a stable procedure for covering skull defects, even those of large dimensions. An added advantage is the significant reduction in effort required to prepare the area of the bone margins compared to other current techniques of cranioplasty.